[OP.4B.04] LONGITUDINAL CHANGES IN LEFT VENTRICULAR STRUCTURE AND DIASTOLIC FUNCTION IN RELATION TO ARTERIAL PROPERTIES IN A GENERAL POPULATION. (September 2016) - Cauwenberghs, N.; Knez, J.; D'hooge, J.; Thijs, L.; Yang, W.Y.; Haddad, F.; Staessen, J.A.; Kuznetsova, T.
Abstract : Objective: Serial imaging studies are needed to clarify the relation of change in left ventricular (LV) structure and function with arterial stiffness. In this longitudinal population study, we assessed in continuous and categorical analyses to what extent arterial properties predict alterations in echocardiographic indexes reflecting LV structure and function. Design and method: In 607 participants (50.7% women; mean age, 50.7 years), using conventional echocardiography and tissue Doppler imaging, we measured LV dimensions, transmitral blood flow and mitral annular tissue Doppler velocities at baseline and after 4.7 years. Using applanation tonometry, we assessed augmentation pressure (AP), central pulse pressure (cPP) and carotid-femoral pulse wave velocity (PWV) at baseline. Standardized effect size was expressed as percent of changes in standard deviation (SD) of δ echocardiographic indexes associated with 1-SD increase in baseline arterial indexes. Results: The clinical correlates of δLV indexes included baseline LV index, age, sex, body mass index, mean blood pressure, pulse rate and changes over time in these co-variables. After full adjustment, longitudinal increase in LV septal (standardized effect size: +14.6%; P = 0.0017) and posterior wall (+13.3%; P = 0.0015) thickness was significantly associated with higher PWV at baseline, whereas LV internal diameter (−12.2%; P = 0.014) decreased with PWV. Consequently, a greater increase in relative wall thickness was associated with baseline PWV (+17.2%; P < 0.0001). We observed similar longitudinal increase in LV wall thickness in relation to higher baseline PWV in men and women. In adjusted logistic analysis, higher baseline PWV was associated with a 156% increase in the odds of developing LV concentric remodeling during follow-up as compared to participants who improved LV geometry (P = 0.0088). Furthermore, in women, a higher baseline cPP predicted a greater increase in LV mass (+18.1%, P = 0.018) and E/e' ratio (+25.8%, P = 0.0064). Conclusions: The key finding of this study is that longitudinal increase in LV relative wall thickness was associated with higher baseline PWV, measure of arterial stiffness. Moreover, in women, a higher cPP predicted worsening of LV diastolic function. Our study demonstrated the importance of arterial properties as a mediator of LV concentric remodeling in men and women, and diastolic dysfunction in women.